2008
DOI: 10.1016/j.peptides.2008.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Activation of endothelial nitric oxide synthase is critical for erythropoietin-induced mobilization of progenitor cells

Abstract: The present study aimed to define the ability of erythropoietin (EPO) to mobilize hematopoietic stem cells (c-kit + /sca-1 + /lin-1 − ; KSL cells) and hematopoietic progenitor cells (CD34 + cells), including vascular endothelial growth factor receptor 2 expressing hematopoietic progenitor cells (CD34 + / Flk-1 + cells). We also sought to determine the role of endothelial nitric oxide synthase (eNOS) in EPO-induced mobilization. Wild type (WT) and eNOS −/− mice were injected biweekly with recombinant erythropoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 31 publications
2
41
0
1
Order By: Relevance
“…Epo promotes proliferation (40,196), inhibits apoptosis (199), and facilitates differentiation of EPCs (200)(201)(202)(203). Furthermore, Epo induces mobilization of EPCs into the circulation (204,205), and their homing (155,206,207). Increased eNOS expression and BH4 biosynthesis has been shown in Epo-treated EPCs and vascular cells ( Fig.…”
Section: Epo In Treatment Of Cardiovascular Diseasesmentioning
confidence: 86%
See 1 more Smart Citation
“…Epo promotes proliferation (40,196), inhibits apoptosis (199), and facilitates differentiation of EPCs (200)(201)(202)(203). Furthermore, Epo induces mobilization of EPCs into the circulation (204,205), and their homing (155,206,207). Increased eNOS expression and BH4 biosynthesis has been shown in Epo-treated EPCs and vascular cells ( Fig.…”
Section: Epo In Treatment Of Cardiovascular Diseasesmentioning
confidence: 86%
“…Increased eNOS expression and BH4 biosynthesis has been shown in Epo-treated EPCs and vascular cells ( Fig. 2; pathway 4) (205,208). Interestingly, recent studies on hypoxic endothelial cells have shown that VEGFR2 can also become an additional component for the EpoR/bCR complex that is essential for NO production (reviewed by ref.…”
Section: Epo In Treatment Of Cardiovascular Diseasesmentioning
confidence: 90%
“…It has previously been noted that NO is also involved in EPO-induced mobilization. 27 As there is crosstalk been NO and O 2 -, some interaction between the two systems cannot be excluded. Endothelial NO synthase expression in EPCs, however, is very low and thus probably endothelial cells in the vascular niche of the bone marrow are important targets for EPO-induced NO production and are involved in the release of EPCs.…”
Section: Discussionmentioning
confidence: 99%
“…endothelial progenitors, 9 and first data indicates a potential role in the proliferation and mobilization of hematopoietic stem cells. 10 Thus, further sets of experiments have to clarify whether the here newly identified effects of Ang-(1-7) are also NO-mediated.…”
Section: In Vivo Ang-(1-7) Effects On Human Mononuclear Cells In Micementioning
confidence: 90%